Application of comprehensive geriatric assessment in health management of older patients with grade Ⅲ to Ⅳ mixed hemorrhoids undergoing surgery - Jiang Zhiyuan; Zhong Shibiao; Tang Li; Li Zhen (结直肠肛门外科)
[Objectives] To investigate the application of comprehensive geriatric assessment (CGA) in the health management of older patients with grade Ⅲ to Ⅳmixed hemorrhoids undergoing surgery. [Methods] Sixty older patients with grade Ⅲ to Ⅳ mixed hemorrhoids treated at the Department of Anorectal Surgery at our hospital between January and October 2021 were recruited and randomly assigned to the control group (n=30) and the treatment group (n=30). Patients in the control group received routine assessment and nursing before and after surgery, while those in the treatment group received CGA within 72 hours after admission on the basis of the control group, and personalized intervention tailored to their geriatric syndromes. The followings were compared between the two groups: indices related to the surgery [time to the first postoperative flatulence, time to the first bowel movement, time to off-bed activities, visual analogue scale (VAS) score, duration of hospitalization, and hospitalization expenses], postoperative complications (postoperative incision edema, urinary retention, and bleeding), satisfaction of health management, and quality of life. [Results] Compared with the control group, the treatment group had significantly shorter time to the first postoperative flatulence, time to the first bowel movement, and time to off-bed activities, shorter duration of hospitalization, lower VAS score, and less hospitalization expenses (P<0.05). There were no significant differences in the incidence of postoperative incision edema and bleeding between the two groups (P>0.05). The incidence of urinary retention in the treatment group was lower than in the control group (P<0.05). The satisfaction of health management in the treatment group was significantly higher than that in the control group (P<0.05). Before intervention, there were no significant differences between the two groups’scores of illness, physical strength, general living conditions, medical conditions, working conditions& interpersonal conditions, and social social-psychological conditions (P>0.05). After intervention, the above scores in the treatment group were higher than those before intervention, and were higher than those in the control group (P<0.05). [Conclusion] The application of CGA for the health management of older patients with grade Ⅲ to Ⅳ mixed hemorrhoids can effectively shorten the duration of hospitalization, reduce hospitalization expenses and the incidence of postoperative complications, increase patients’satisfaction and quality of life. It is worthy of clinical promotion and application.